Comparison of Effectiveness Between Nebivolol and Bisoprolol in Treating Hypertensive Patients (The Journal of Ad-din Women's Medical College, 2023)
Hypertension is the leading cause of cardiovascular disease. Beta blockers are prescribed for hypertension, heart failure, angina pectoris or a history of myocardial infarction. In this study, we have compared the effectiveness between two beta blockers, i.e. Nebivolol and Bisoprolol in hypertensive patient. A randomized prospective study was conducted from 1st January to 31st July 2022 at Jashore Medical College Hospital, Jashore in the outpatient department of medicine after maintaining all ethical issues. Five hundred twenty eight hypertensive patients without other comorbidities were studied after informed written consent. Patients were followed up for three months. Out of 528 patients 264 were received Nebivolol. In this case group 40 patients were missed in follow up. And among 224 patients, 198 patients were found optimum reduction of blood pressure which was 88.39% out of 224. Rest 264 were received Bisoprolol. In this case group 58 patients were missed in follow up. And among 206 patients, 176 patients were found optimum reduction of blood pressure which was 85.43% out of 206. In this study Nebivolol showed superiority in reduction of blood pressure in comparison to Bisoprolol that is 2.95%. Large scale trials along with comorbidities, mortality and hospital stay reduction as well as strict follow up are needed to compare various beta blockers.The Journal of Ad-din Women's Medical College; Vol. 11 (1), Jan 2023; p 33-37